Chromium histidinate improves serotonergic properties and carbohydrate metabolism in rat models of insulin resistance and of type 2 diabetes - Komorowski, James Richard; Şahin, Kazım; Tuzcu, Mehmet; Şahin, Nurhan; Akdemir, Fatih; Juturu, Vijaya (Federation Amer Soc Exp Biol, 2009)
[Abstract Not Available]